Calendaring for Wide Area Networks - Menache, Ishai; Kandula, Srikanth; Schwartz, Roy; Babbula, Spandana Raj (ACM SIGCOMM, 2014)
Datacenter WAN traffic consists of long-term high priority transfers that have to be carried as soon as they arrive alongside large transfers with pre-assigned deadlines on their completion (ranging from minutes to hours). The ability to offer guarantees to large transfers is crucial for business needs and impacts overall cost-of-business. State-of-the-art traffic engineering solutions only consider the current time epoch and hence cannot provide pre-facto promises for long-lived transfers. We present TEMPUS, an online traffic engineering scheme that exploits information on transfer size and deadlines to appropriately “pack" long-running transfers across network paths and time, thereby leaving enough capacity slack for future high-priority requests. TEMPUS builds on a tailored approximate solution to a mixed packing-covering Linear Program, which is parallelizable and scales well in both running time and memory usage. Consequently, TEMPUS is able to quickly and effectively update its solution when new transfers arrive or unexpected changes happen. These updates involve only small “edits" to existing transfers. Therefore, as experiments on traces from a large production WAN show, TEMPUS can offer and keep promises to long-lived transfers well in advance of their actual deadline; the promise on minimal transfer size is comparable with an offline optimal solution and outperforms state-of-the-art solutions by 2-3X. ​